A novel polyphenolic prebiotic and probiotic formulation have synergistic effects on the gut microbiota influencing Drosophila melanogaster physiology. (5th November 2018) - Westfall, Susan; Lomis, Nikita; Prakash, Satya
Abstract: The gut microbiota is a vast community of synergistic bacterial species providing health benefits to the host. Imbalances in the gut microbiota (dysbiosis) due to diet, antibiotic use, age and stress contribute to disease development including diabetes, obesity, colon cancer, inflammatory bowel disease, inflammaging and neurodegeneration. Fortunately, a probiotic regime with a diet rich in prebiotics may reverse dysbiosis promoting health and wellness in age. The current study designs, optimizes and tests a novel probiotic and synbiotic formulation consisting of three metabolically active probiotics Lactobacillus plantarum, Lactobacillus fermentum and Bifidobacteria infantis together with a novel polyphenol-rich prebiotic, Triphala. The prebiotic action of Triphala was characterized using in vitro batch cultures, Drosophila melanogaster and a simulated model of the human gastrointestinal tract (SHIME) where in each model, Triphala supported growth of beneficial bacteria while inhibiting pathogenic species. Neither Triphala at 0.5% w/v nor the individual probiotics at 5.0 × 10 8 to 7.5 × 10 9  CFU/ml demonstrated toxicity in Drosophila . Interestingly, motility was combinatorially enhanced by the probiotic and synbiotic formulations reflecting the beneficial variations in the gut microbiota. Altogether, the present study shows that probiotics and synbiotics in combination are more effective at modulating the gut microbiota and eliciting biological effects than their components.